Ubhauli and Udhuali: Application of Symbolic Ecology and Ecological Symbolism in Kirat-Rai in Eastern Nepal - Dahal, Bishnu Prasad (Patan Pragya, 2021)
The aim of this article is to explore how the Ubhauli and Udhauli are functioning as a mechanism to maintain the socio-cultural and economic-ecological balance between populations and resources with the help of symbolic and ecological perspectives These great and holy festivals of KiratRais through which they can understand symbolic ecology and ecological symbolism in Kirat world through which Kirat can easily understand the nature, ecology and culture for their adaptation. Ubhauli and Udhauli festivals offer the social harmony, solidarity, integration through the socialization and such entertainment; works as mechanism of conflict resolution in socio-cultural, religious, ecological, economically, linguistically etc. to cope with the existing environmental, cultural and social problems of the Kirat world. The festivals Ubhauli and Udhauli are celebrated twice in a year. April and November are the celebrating months which appear through seasonal changes that help to bring society in order through repetitions and re-beginnings.